Tick-borne pathogens in removed ticks Veneto, northeastern Italy: A cross-sectional investigation. Issue 26 (November 2018) - Beltrame, Anna; Laroche, Maureen; Degani, Monica; Perandin, Francesca; Bisoffi, Zeno; Raoult, Didier; Parola, Philippe
Abstract: Background: In Italy, the incidence of tick-borne diseases in humans is underestimated, as they are not obligatorily notifiable. The aim of this study was to investigate the presence of tick-borne pathogens in ticks removed from human subjects in Veneto region (northeastern Italy), an area for which no published studies are yet available. Method: Forty-five ticks prospectively removed from human subjects, between March and August 2016, were analysed for bacterial DNA. Results: Seven of 45 ticks were infected with bacteria, including human pathogens: 4 Rickettsia spp. (9%), including R. monacensis and R. helvetica ; 3 Borrelia spp. and 1 Anaplasma phagocytophilum . Three subjects bitten by infected ticks reported symptoms. Conclusions: Rickettsiosis and anaplasmosis, tick-borne diseases previously not considered in northeastern Italy, should not be neglected. A new survey for a longer period is required to obtain stronger epidemiological data.